2007
DOI: 10.1134/s181123820703006x
|View full text |Cite
|
Sign up to set email alerts
|

Cyanoacrylate-based adhesives

Abstract: The effect the curing conditions on the properties of adhesive joints formed using cyanoacrylatebased adhesives is investigated. The temperature dependences of relative rigidity and mechanical loss tangent are studied by torque analysis for poly(ethyl-, allyl-, allyloxyethyl-, allyloxyisopropyl-, propargyloxyethyl-, and propargyl-) cyanoacrylates after their thermal treatment in the temperature range of 20-250 ° C. The glass transition parameters of polycyanoacrylates and the dependence of the curing intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
2
0
2
Order By: Relevance
“…The decrease in the shear strength values of the post-cured joints made with ECN is in agreement with previously reported studies made with composite-ethyl cyanoacrylate [6] and steel-ethyl cyanoacrylate [7] joints. The decrease in the shear strength values of the joints made with ECN after being post-cured can be related to Figure 7.…”
Section: Influence Of the Post-cure Temperature Of Pecn On The Adhesisupporting
confidence: 92%
See 2 more Smart Citations
“…The decrease in the shear strength values of the post-cured joints made with ECN is in agreement with previously reported studies made with composite-ethyl cyanoacrylate [6] and steel-ethyl cyanoacrylate [7] joints. The decrease in the shear strength values of the joints made with ECN after being post-cured can be related to Figure 7.…”
Section: Influence Of the Post-cure Temperature Of Pecn On The Adhesisupporting
confidence: 92%
“…Furthermore, the solvent used as polymerization initiator determined the nanoparticle size and the polydispersity of poly(ethyl cyanoacrylate)s. These results have been explained by the co-existence of two different polymerization mechanisms, i.e., interfacial precipitation of pre-formed polymer and interfacial polymerization. The influence of the temperature on the polymerization of ethyl cyanoacrylate has been studied elsewhere [2][3][4][6][7][8], but different conclusions have been obtained depending on the polymerization conditions. For example, the particle size of poly(ethyl 2-cyanoacrylate)s (pECNs) has been related to the polymerization temperature by Reddy et al [2] whose have demonstrated that the higher was the polymerization temperature, the larger was the polymer particle size because of some agglomeration of particles was produced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los iones metálicos presentes en coordinación con el material depositado, mejoran la reactividad del doble enlace de la molécula del 2-cianoacrilato, por lo que la reacción de polimerización se ve favorecida. Este proceso produce un polímero lineal de estructura regular tipo cabeza-cola en los que se ven favorecidos enlaces entre radicales metil, etil, butil y alil de 2-cianoacrilatos, especialmente en la producción de adhesivos comerciales [3].…”
Section: Aditivosunclassified
“…Los reactivos de curado frecuentemente presentan tres o más grupos funcionales por molécula. El agente de curado debe tener muchos grupos funcionales dado que favorecen el entrecruzamiento de las cadenas [3].…”
Section: Introductionunclassified